The Routledge Handbook of Comparative Economic Systems - Dallago, Bruno; Casagrande, Sara (Taylor & Francis, 2023)
The 2020 pandemic and likely even more the renewed East-West clash epitomized by the Russian invasion of Ukraine and the West's reaction to it. The handbook is divided into five parts. Each part deals with an issue of relevance for the discipline. The first and second parts look at the subject, content and approach of the discipline and its comparative method. The third part looks at the idiosyncratic nature of different economic systems and their constituent elements. The fourth part considers the outcomes that different economic systems generate and how these outcomes change following the evolution and transformation of economic systems. The last part takes stock and looks ahead at the challenges, from a theoretical and applied perspective, and the exogenous and endogenous factors promoting the advancement of the discipline, including the interaction between and competition among varied approaches and opposing paradigms.